Educational Attainment and the Effect of Intensive Blood Pressure Reduction: A Post Hoc Analysis of the SPRINT Study - Joshua Garfein; Akira Sekikawa; Andrew Mrkva; Djhenne Dalmacy; Jarett D. Berry; Yordanos M. Tiruneh; Jared W. Magnani (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2025)
Background Hypertension is a major risk factor for cardiovascular disease (CVD). The SPRINT (Systolic Blood Pressure Intervention Trial) study demonstrated that intensive lowering of systolic blood pressure (SBP) targeting <120 mm Hg reduced cardiovascular disease risk and all‐cause death among high‐risk patients with hypertension. The link between education and cardiovascular health is well documented, but it remains unclear whether the effect of intensive SBP reduction differs by education. Methods We included 9361 SPRINT participants, stratified by education (less than college, some college through college graduate, and greater than college degree). We examined the effect of intensive SBP lowering across educational strata in relation to both SBP achieved and the composite cardiovascular SPRINT end point using multivariable proportional hazards models. Results Participants' average age was 67.9±9.4 years, with 35.6% women and 57.8% White race; 24.4% received greater than a college degree and 33.7% had less than a college education. Those with higher education were more likely to be older, men, and White race. During follow‐up, SBP was nearly identical across categories of education. Education was associated with a dose–response reduction in the composite end point after intensive SBP lowering, particularly among non‐Black individuals (highest to lowest education: adjusted hazard ratios, 0.44 [95% CI, 0.29–0.66]; 0.82 [95% CI, 0.60–1.12]; and 0.88 [95% CI, 0.63–1.22]; P interaction=0.01). Among Black participants, the association of SBP lowering with the composite end point did not differ significantly by education. Conclusions Despite similar SBP, higher education was associated with a larger improvement in cardiovascular outcomes following intensive SBP reduction, with differences by race. These findings highlight the relevance of social factors such as education in the generalizability of clinical trials.